The New European Normative And Legal Framework For The Protection Of Injured Parties In Motor Vehicle Liability Insurance In Case Of Insolvency Of The Insurer - Željka Primorac; Mirela Karmen Lučev (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In this paper, the authors start from the origin of the provisions on the effects of the insurer's insolvency on the legal position of injured parties in compensation procedures in motor vehicle liability insurance. Pointing to their particularity, but also the inadequate scope of protection of the injured parties in case of insolvency of the injured party's insurer or the cessation of insurance (with special reference to the analysis of the judgment of the European Court of Justice in case C-409/11), the authors point to the valid provisions of the newly established insurance system of civil liability with regard to the use of motor vehicles and the enforcement of the obligation to insure against such liability (according to the provisions of Directive (EU) 2021/2118) and the corresponding implementation of these into the national legal system by the Act amending the Compulsory Traffic Insurance Act from 2023.